2023
DOI: 10.1021/acs.jpclett.2c03287
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Wavelength-Dependent Emission Behavior in (NH4)2SnCl6 via Sb3+ Dopant

Abstract: With high photoluminescence efficiency and a simple solution synthesis method, lead halide perovskites are expected to be a promising material for display and illumination. However, the toxicity and environmental sensitivity of lead hinder its potential applications. Here, we introduced Sb 3+ ions into the lead-free perovskites derivative (NH 4 ) 2 SnCl 6 via a doping strategy. For the first time we synthesis the excitation-dependent perovskite with dynamically tunable fluorescence from yellow to near-infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…The absorption near band-edge is much enhanced by the Sb triplet state nearby indicating that Sb ion orbitals have a great contribution to absorption. 15 Moreover, the calculated bandgap via the Tauc equation decreases gradually with the increasing Sb 3+ concentration (Fig. S9, ESI †), which is consistent with the extended absorption range at higher Sb 3+ doping content (Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The absorption near band-edge is much enhanced by the Sb triplet state nearby indicating that Sb ion orbitals have a great contribution to absorption. 15 Moreover, the calculated bandgap via the Tauc equation decreases gradually with the increasing Sb 3+ concentration (Fig. S9, ESI †), which is consistent with the extended absorption range at higher Sb 3+ doping content (Fig.…”
Section: Resultssupporting
confidence: 76%
“…14 Recently, Lin et al successfully incorporated Sb 3+ into the (NH 4 ) 2 SnCl 6 lattice and achieved emission at 690 nm which is derived from the STEs of SbCl 5 . 15 These facts confirm that Sb 3+ with an 5s 2 electron is an excellent and potential dopant. However, although the Sb 3+ ions have been successfully inserted into the lattice, highly efficient Sb-doped organic indium bromides with [SbBr 5 ] 2− pyramids have not been widely reported and the relationship between their structures and photophysical properties has not been fully understood.…”
Section: Introductionmentioning
confidence: 55%
“…Then what is the source of the sideband emission state ES3 at 740 nm? In an early report, we found an independent DAP band in Sb doped NH 4 SnCl 4 56 because of the clear difference of electronegativity and electronic density of Sb and Sn ions as well as close separation in halides. Therefore the 740 nm band may be the Sn and Sb site charge-transfer radiation transition between the SbCl 5 site(D) and Sn site(A).…”
Section: Resultsmentioning
confidence: 83%
“…Sb-doped OIMHs have been reported to emit blue, orange, or white light, with many applications for near-infrared emission. These findings indicate that appropriate ion doping can break the parity prohibition and induce carrier-absorption transitions, thereby generating colored luminescence. , Noculak et al synthesized Cs 2 MInCl 6 : x Sb (M = Na, K, x = 0–100%) with efficient broadband blue emission (Na, PLQY = 82%) and green emission (K, PLQY = 93%) . Kshirsagar et al reported that Sb 3+ -doped Cs 2 InCl 5 ·H 2 O exhibits highly efficient and strong temperature-dependent green luminescence .…”
Section: Introductionmentioning
confidence: 99%